APLIKASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI POKOK CIRI-CIRI MAKHLUK HIDUP - Hapni Hapni (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract: Teacher centered, monotone class dan less interaction between teacher and students were the trend of learning activities. By these situation students become passive learners, less motivation, loss of concentration, and easily bored. In some material such as The Characteristics of living things, students’ achievement is getting lower. Through this research, Researcher tries to cope with the problem by conducting Class Action Research. In this research, Group Investigation is implemented to learn Caracteristics of living things material. The research was established in two cycles, the first cycle consists of two learning activities, and the second cycle consists of one learning activity. The purposes of the study are (1) practicing teacher ability, (2) increasing student activity, (3) increasing students’ achievement, (4) detecting student respond. The subject are 37 students of the 7th grade A class of SMPN 27 Banjarmasin. Data was collected by observation, test administration, and questionnaire. Analyzing data was conducted by qualitative descriptive. The research showed that (1) Practicability of lesson plan in the first cycle is 96,44% (good), and in the second cycle is 100% (good); (2) Students learning activity in the first cycle is ranging from 81,48% to 100% for the positive activities and 9,27 % for the irrelevance activities. In the second cycle students learning activity is ranging from 96,30% to 100% for the positive activities. (3) In the first cycle, students achievement is 76,75 on average with the class mastery 75,68%, and in the second cycle increase to 81,08 with the class mastery 100%; (4) Students give positive respond to the learng activities.Key words: students achievement, Group Investigation Models, caracteristics of living things material